PEMBUATAN VIDEO ANIMASI “GREEN TOURISM” DALAM UPAYA MENGURANGI PERMASALAHAN SAMPAH PLASTIK - Ramadhani, Nurul Fathya Rahma Puspita (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2022)
A tourist attraction serves as a recreational vacation destination for both locals and foreign tourists. Tourism is therefore encouraged to grow as a result of this condition. However, there is an accumulation of plastic waste in tourist attractions. According to NatGeo's research, plastic waste was found at Kedonganan Beach, Bali, in 2019. A projection indicates that in 2050 there will be an accumulation of 12 trillion plastic wastes if the accumulation of plastic wastes is not prevented. The lack of care and awareness between the community, government and managers makes tourist attractions polluted. The amount of waste also makes the community around the tourist attractions directly affected. Therefore, it is necessary to educate about the prevention of plastic waste accumulation. Through, animated video media becomes an intermediary media for delivering information. This animation can help realize how important it is to preserve nature, especially tourist attractions to the community.